Censo de adultos mayores en situación de calle Medellín 2009 (2009)
ABSTRACT: From the Sixties of the last century, the country has undergone great demographic changes and of space redistribution of the population. Of being a country with high levels of population increase, rates of 30 by thousands at that time, today passed to a situation of stagnation with rates of growth inferiors to 17 through thousands. Of a country with a 48% of rural population, one became a country with predominance of the life in the urban zones, which lodge more of 72% of their inhabitants. The third part of the national population is concentrated in the 5 great urban nuclei. These changes, combined to the displacement of the population of their places of origin and to the social decomposition by the situation of conflict for several decades, have created propitious conditions for the increase of people in street situation, where they search carefully the subsistence in the public space. The knowledge of the phenomenon and its dynamics requires of up-to-date and reliable information. Its magnitude, the basic characteristics of the population, the real conditions of life and the familiar surroundings. Of, for example, it is possible there to deduce the indispensable budget so that the policies of treatment, prevention and reintegration of those inhabitants to their familiar nucleus and the society are effective generally.